Degree of call synchrony during interactions between male snowy tree crickets - (:unkn) unknown (My University, 1990)
Call synchrony has been reported for the snowy tree cricket (Oecanthus fultoni), but the degree to which it occurs in natural interactions has not been previously investigated. I recorded acoustic interactions among ten pairs of male snowy tree crickets to determine the degree to which call synchrony occurs. High levels of call synchrony (percent of calls that temporally overlapped another call) were found in all pairs, but in only half of the pairs was synchrony greater than expected by chance. Males differed considerably in their tendency to temporally overlap the calls of their neighbors. There was minimal frequency overlap of calls in all pairs. Avoidance of frequency overlap may have allowed calls of individual males to be distinguished when there was temporal overlap.
Keywords: call synchrony; snowy tree crickets; Oecanthus fultoni; Orthoptera